Correction: Reproductive genetic carrier screening for cystic fibrosis, fragile X syndrome, and spinal muscular atrophy in Australia: outcomes of 12, 000 tests. (November 2018) - Archibald, Alison Dalton; Smith, Melanie Jane; Burgess, Trent; Scarff, Katrina Louise; Elliott, Justine; Hunt, Clare Elizabeth; Barns-Jenkins, Caitlin; Holt, Chelsea; Sandoval, Karina; Kumar, Vanessa Siva; Ward, Lisa; Allen, Emily Caroline; et al.
Zoe McDonald, BSc, was omitted from the list of article coauthors. Her name should have been included as the seventh author, following Clare Elizabeth Hunt. Her affiliation is Victorian Clinical Genetics Services, Parkville, Victoria, Australia. The authors regret the error.